ANALISIS KERAGAAN GENETIK JAGUNG TOLERAN CEKAMAN KEKERINGAN DI LAHAN SAWAH TADAH HUJAN - Eko Ilmawan; St. Subaedah; A. Takdir (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
This study aims to evaluate the genetic performance of 8 corn genotypes that are tolerant of drought stress. The study was conducted at the Experimental Garden, Bajeng, Gowa Regency, South Sulawesi. The research was carried out using a Split Plot Design method. As the main plot is a water stress treatment consisting of no stress, moderate stress and severe stress. As a subplot is a prospective hybrid corn genotype consisting of 8 genotypes and two comparative varieties namely Bima 3 and Bima 7. The results of this study indicate that Genotype G7 is the highest genotype for plants, Genotypes G2 and G5 are genotypes with, silking interval anthesis (ASI ) the smallest and fastest harvesting age. The G3 genotype is the genotype with the longest root.